The Role of Architecture Exhibitions in Introducing Architecture to the Community - Rizka Felly; Reza Arlianda; Muhammad Fahri; Helfa Rahmadyani; Andina Syafrina (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
An architecture exhibition serves as an important platform for professionals in architecture, designers, academics, and the community. This event is utilized as a space to gather, discuss, and share views on the development of the architectural world. The exhibition functions as a medium to showcase ideas, both those that have been built and those still in conceptual form. In addition to providing an opportunity for architecture students and professional architects to demonstrate their skills and creativity, the exhibition also aims to educate the community about the importance of architectural design in enhancing the quality of life. Exhibitions serve as a form of outreach, promoting the archive to current and potential users, visitors, stakeholders, and administrators. This community service activity occurred at the Department of Architecture in Bangka Belitung. The method employed includes several stages: preparation, curation of works, collaboration with partners, execution, and evaluation. The exhibition successfully attracted public interest and served as a means to introduce and educate the public about architecture. A total of 324 people were recorded as having visited the exhibition in two days.